Flamelet regime characterization for non-premixed turbulent combustion simulations - Chan, Wai Lee (2018)
Regime characterization has been shown to be an insightful technique in the study of turbulent combustion, providing useful information about the relation between fundamental combustion modes and physical scales that require consideration. Regime diagrams can guide the appropriate utilization of combustion models, which is critical for the accuracy of numerical simulations of turbulent reacting flows. In the present study, a flamelet regime diagram is developed to assess the applicability of various diffusion flamelet models with respect to the local grid resolution and underlying flow/flame structure. The flamelet regime parameter is defined such that it can be unambiguously determined with fully resolved data, as in the case of direct numerical simulations (DNS), and adequately estimated from filtered information of large-eddy simulations (LES). To this end, the flamelet regime diagram is studied through an a priori analysis of a DNS dataset of a turbulent lifted hydrogen jet flame in a heated coflow. Findings from this analysis verify the length-scale arguments that are based on the concepts of inner-reaction zone thickness and dissipation element, upon which the regime diagram is constructed on. In addition, the relevance of the regime diagram to the numerical grid size enables it to act as a guiding tool for model selection in non-premixed combustion LES.